Case Report: Treatment of a complex hand disfigurement injury by fully shaped reconstruction of a severed finger combined with ectopic banking - Jia, Zhengfeng; Shi, Longbao; Gao, Weilu; Li, Han; Zhang, Jianzheng; Shi, Weidong; Li, Jiantao; Zhao, Jianwen (Frontiers in Surgery, 2024)
One of the primary challenges in hand microsurgical reconstruction lies in addressing severe hand injuries, particularly those involving multiple finger amputations, as autologous replantation might not fully restore hand functionality. In such scenarios, fully shaped reconstruction of a severed finger combined with Ectopic banking could yield superior reconstructive outcomes and enhance the amputated limb's function. This case report presents a unique approach that combines ectopic replantation of an amputated finger with interphalangeal reconstruction methods to restore both the form and function of the hand. A 43-year-old female patient suffered an injury to her left hand, leading to ischaemic amputation of all four fingers. Our treatment strategy involved a blend of allograft reimplantation, interdigital reconstruction, iliac bone grafting, and metacarpophalangeal joint fusion to revive the hand's functionality. A year post-surgery, the toe-to-finger reconstructions of the left thumb and middle finger exhibited excellent survival, although the ring and little fingers were lost. The flap located on the dorsum of the left foot healed seamlessly, with uninterrupted blood flow to the toe tips and no complications. As a result, the patient retained three fingers and regained functional activity. Our study underscores that the synergistic approach of fully shaped reconstruction of a severed finger combined with Ectopic banking not only elevates surgical efficiency but also significantly bolsters hand morphology and function. This case report underscores the significance of the Treatment of a complex hand disfigurement injury by fully shaped reconstruction of a severed finger combined with Ectopic banking in the realm of finger reconstruction, highlighting their transformative potential in restoring hand function and appearance.